Correlations Analysis of Airport Sustainability and Local Government Budget - Setiawan, Mohd ikhwan; Dhaniarti, Iswachyu; Hasyim, Cholil; T Atamaja, Wahyu Mahendra; Mulyo Utomo, Wayhu; Sugeng, Sugeng (International Journal of Integrated Engineering, 2018)
The development of a public private partnership business centre in the region, particularly in the airport area, will improve regional economic equity. This study aims to analyse the correlation between airport sustainability and local government budget in Indonesia. The method used in this research is mixed method research. The results indicate that a cooperation agreement between the local government and the airport management will generate mutual benefits for both parties. Airport managers can improve their services to consumers and local governments receive contributions during the term of the agreement. Based on the T-Value Test Result, the T-value for the Airport Performance variable is 0.694. T-Value Test Results and compared with T-table equal to 1,976 (significant level 0,05) hence T-count <T-table thus variable of Airport Performance is predicted not to have a significant correlation to Local Government Budget (APBD) Performance. Regional governments are expected to participate more actively in investments or asset sharing of airports in the region.